Interactions between private and public sector wages - Afonso, António (2022)
We examine the interactions between public and private sector wages per employee in OECD countries. The growth of public sector wages and of public sector employment positively affects the growth of private sector wages. Moreover, total factor productivity, the unemployment rate and the degree of urbanisation are also important determinants of private sector wage growth. With respect to public sector wage growth, we find that it is influenced by fiscal conditions in addition to private sector wages. We then set up a dynamic labour market equilibrium model with two sectors, search and matching frictions and exogenous growth to understand the transmission mechanisms of fiscal policy. The model is quantitative consistent with the main estimation findings.